TUMOR MARKERS EXPRESSION LEVELS IN GASTRIC CANCER PATIENT’S PERIPHERAL BLOOD BY RT-PCR ASSESSMENT - Gabriel da Silva KAWAKAMI; Marina Alessandra PEREIRA; Márcia Saldanha KUBRUSLY; Alexis Germán Murillo CARRASCO; Marcus Fernando Kodama Pertille RAMOS; Ulysses RIBEIRO JÚNIOR (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2024)
ABSTRACT BACKGROUND: Hematological recurrence is the second most frequent cause of failure in the treatment of gastric cancer. The detection of circulating tumor markers in peripheral blood by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) method may be a useful tool to predict recurrence and determine the patient’s prognosis. However, no consensus has been reached regarding the association between the tumor markers level in peripheral blood and its impact on patient survival. AIMS: To evaluate the expression of the circulating tumor markers CK20 and MUC1 in peripheral blood samples from patients with gastric cancer by qRT-PCR, and to verify the association of their expression levels with clinicopathological characteristics and survival. METHODS: A total of 31 patients with gastric adenocarcinoma were prospectively included in this study. CK20 and MUC1 expression levels were analyzed from peripheral blood by the qRT-PCR technique. RESULTS: There was no statistically significant (p>0.05) association between CK20 expression levels and clinical, pathological, and surgical features. Higher MUC1 expression levels were associated with female patients (p=0.01). There was a correlation between both gene levels (R=0.81, p<0.001), and CK20 level and tumor size (R=0.39, p=0.034). CONCLUSIONS: CK20 and MUC1 expression levels could be assessed by qRT-PCR from total peripheral blood samples of patients with gastric cancer. CK20 levels were correlated to MUC1 levels as well as to tumor size. There was no difference in disease-free survival and overall survival regarding both genetic markers expression in this series.